Lao People's Democratic Republic : Recent Economic Developments. (IMF Staff Country Reports; Country Report, 1998)
This paper describes economic developments in Lao People's Democratic Republic (PDR) during the 1990s. Economic reforms in Lao PDR that started in 1986 were supported by IMF arrangements in 1989-97. During those years, the economy grew annually at 5 percent to 8 percent and through prudent macroeconomic policies, the government managed to achieve broadly stable macroeconomic conditions. Meanwhile, structural reforms took shape, so that market processes are now at work in most segments of the economy. However, in 1997, economic conditions deteriorated and progress in structural reform slowed significantly.